Functional connectivity impairment of thalamus-cerebellum-scratching neural circuits in pruritus of chronic spontaneous urticaria - Zhang, Leixiao; Zou, Zihao; Yu, Siyi; Xiao, Xianjun; Shi, Yunzhou; Cao, Wei; Liu, Ying; Zheng, Hui; Zheng, Qianhua; Zhou, Siyuan; Yao, Junpeng; Deng, Yanli; et al. (Frontiers in Neuroscience, 2022)
Pruritus of chronic spontaneous urticaria (CSU) is one of the most common and irritating sensations that severely affects the quality of life. However, the changes in the functional connectivity (FC) between thalamic subregions and other brain regions have not been fully elucidated. This study aimed to explore the potential changes in brain neural circuits by focusing on various subregions of the thalamus in patients with CSU pruritus to contribute to the understanding of chronic pruritus from the perspective of central mechanisms. A total of 56 patients with CSU and 30 healthy controls (HCs) completed the data analysis. Urticaria Activity Score 7 (UAS7), pruritus visual analog score (VAS-P), Dermatological Life Quality Index (DLQI), and immunoglobulin E (IgE) values were collected to assess clinical symptoms. Seed-based resting-state functional connectivity (rs-FC) analysis was used to assess relevant changes in the neural circuits of the brain. Compared to HCs, seeds within the caudal temporal thalamus (cTtha) on the right side of patients with CSU showed increased rs-FC with the cerebellum anterior lobe (CAL). Seeds within the lateral prefrontal thalamus (lPFtha) on the right side showed increased rs-FC with both CAL and pons, while those within the medial prefrontal thalamus (mPFtha) on the right side showed increased rs-FC with both CAL and the dorsal lateral prefrontal cortex (dlPFC) on the right side. Seeds within the posterior parietal thalamus (PPtha) on the right side showed increased rs-FC with the cerebellum posterior lobe (CPL) on the left side. The UAS7 values and IgE levels were positively correlated with the rs-FC of the right dlPFC. Our results suggest that patients with CSU may exhibit stronger rs-FC alterations between certain thalamic subregions and other brain regions. These changes affect areas of the brain involved in sensorimotor and scratching. Trial registration number [http://www.chictr.org.cn], identifier [ChiCTR1900022994].